Photopatternable Poly(dimethylsiloxane) (PDMS) for an Intrinsically Stretchable Organic Electrochemical Transistor - Kang, Joohyuk; Lim, Young-Woo; Lee, Injun; Kim, Seungwan; Kim, Kyung Yeun; Lee, Wonryung; Bae, Byeong-Soo (American Chemical Society, 2022)
Patterning elastomers is an essential process for the application of elastomers to stretchable bioelectric devices. In general, replication of a mold and laser ablation are used for patterning elastomers. However, these methods are inefficient and time consuming due to complex patterning procedures and a heat induced curing mechanism. In this work, we developed a photopatternable elastomer called thiol-ene cross-linked poly(dimethylsiloxane) (TC-PDMS). TC-PDMS showed high -resolution patternability (similar to 100 mu m) through a direct patterning process. It also had high stretchability (similar to-140%) and low Young's modulus (similar to 2.9 MPa) similar to conventional PDMS. To demonstrate its practicability in stretchable bioelectric devices, TC-PDMS was applied to a passivation layer of an intrinsically stretchable organic electrochemical transistor (OECT), which showed a low leakage current (-20 mu A) and a high transconductance (0.432 mS) at high strain (60%). The stretchable OECT was able to record electrocardiographic (ECG) signals from human skin, and the measured ECG signals exhibited a high signal-to-noise ratio of 12.2 dB.